Coloration of Polyester Fibers for Securities Protection from Counterfeit - Goldade, V.A.; Kuzmenkova, N.V.; Sytsko, V.E. (Journal of Research Updates in Polymer Science, 2015)
The results of modifying polyester fibers with luminescent colorants by crazing mechanism have been given. By means of REM and AFM stages of crazes initiation, their transformation into fibrillar structure of fiber and redistribution of modifiers incorporated into crazes in the surface layer of fiber have been revealed. Techniques of concentrating luminescent colorants on local sections of fiber with alternation of unprocessed segments and segments containing target additives have been described. Polyester fibers with alternating by length sections of luminescent division of colors have been obtained. It was shown that effective fiber coloration takes place when the drawing out degree ε* is between 2 and 3. Fibers modified by Oxazine and Rhodamine colorants are characterized by highest intensity of luminescence in UV radiation. The conclusion has been made that technology of modifying chemical fibers by cazing mechanism allowing implementing measured incorporation of target additives on local sections of fiber satisfy in the optimal way the protection criteria of paper filled with such fibers from counterfeiting.